Micheline Coulombe Saint-Marcoux et Marcelle Deschênes : pionnières dans le sentier de la création électroacoustique - Lefebvre, Marie-Thérèse (Circuit : musiques contemporaines, 2009)
A review of “masculine” and “feminine” attitudes towards music composition of the past fifty years highlights the contributions of Micheline Coulombe Saint-Marcoux and Marcelle Deschênes to the development of Québécois electroacoustic music. The author re-creates the historical context for the composers’ childhoods, adolescences, and periods of training in Montreal and Paris, and follows this with a discussion of how they negotiated the dominant trends of the 1970s. She then turns to the composers’ roles as pioneers: in their wish to depart from well-trodden paths, Coulombe Saint-Marcoux and Deschênes turned to new technological tools that would allow them to express a new artistic sensibility. From this perspective, they should be considered the “sherpas” of Québécois electroacoustic music.
Publisher: Les Presses de l'Université de Montréal

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)